Fulvic acid synergistic formula fertilizer and preparation method thereof

Through the combined envelope solution of iron-doped modified titanium dioxide and acrylic grafted low-density polyethylene, the problem of insufficient fertilizer release ability is solved, the effective utilization of nutrients and environmentally friendly fertilizer release is achieved, and water pollution is reduced.

CN119241309APending Publication Date: 2025-01-03ANHUI SMART FERTILIZER TECH CO LTD

Patent Information

Application Number
CN202411483446.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The poor sustained release capacity of existing fertilizers leads to low fertilizer utilization, loss or volatilization of nutrients, and eutrophication pollution in the water.

Method used

The envelope solution is prepared by mixing iron-doped modified titanium dioxide with acrylic acid grafted low-density polyethylene. The stability of the envelope material is improved through physical entanglement and non-covalent bonding, and the yellowic acid glutarization technology is combined with spray drum granulation technology. Effective formula fertilizer to achieve slow release of nutrients.

Benefits of technology

It improves the slow release capacity of fertilizers, reduces nutrient loss and waste, enhances the utilization rate of fertilizers, and reduces environmental pollution through photocatalysis, providing expansion of the light response range and degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098090820000121
    Figure BDA0005098090820000121
  • Figure BDA0005098090820000122
    Figure BDA0005098090820000122
  • Figure BDA0005098090820000131
    Figure BDA0005098090820000131
Patent Text Reader

Abstract

The invention discloses a fulvic acid synergistic formula fertilizer and a preparation method thereof, and belongs to the technical field of fertilizers, the fulvic acid synergistic formula fertilizer comprises the following raw materials by weight: 80-90 parts of fertilizer effect particles and 20-35 parts of a coating solution. The preparation method of the fulvic acid synergistic formula fertilizer comprises the following steps: placing the fertilizer effect particles in a spray drum granulator, coating the surfaces of the fertilizer effect particles with the coating solution in a rotating state, drying in a drying oven at 30 DEG C to obtain the fulvic acid synergistic formula fertilizer, and controlling the particle size of the fertilizer particles to be 4-6mm. The fulvic acid synergistic formula fertilizer prepared by the invention has excellent slow release performance and degradability, promotes the growth of crops, and increases the utilization rate of the fertilizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fertilizers, and in particular relates to a fulvic acid synergistic formula fertilizer and a preparation method thereof. Background Art

[0002] Fertilizers contribute 40%-60% to crop yields. Fertilizer application is an important measure to ensure food security, but the fertilizer utilization rate has long been only around 30%-45%.

[0003] As an active substance, synergistic fertilizer can increase the absorption of nutrients by crops through methods such as nitrogen fixation, and can also play a certain regulatory role in the growth of crops. It is usually added to conventional fertilizers, which can appropriately reduce the amount of fertilizer applied and improve the utilization rate of fertilizers.

[0004] Fulvic acid has significant advantages as a synergistic fertilizer. It can not only improve soil structure, increase nutrient utilization, enhance crop resistance, and regulate soil pH, but also promote crop growth and increase pesticide activity. When fulvic acid is combined with conventional fertilizers, it can greatly improve fertilizer utilization. These advantages make fulvic acid have a wide range of application prospects in agricultural production. However, the above fertilizers have no slow-release function and decompose quickly after application. Only a small amount is absorbed by crops, and the fertilizer utilization rate is low. The remaining nutrients volatilize or are washed away by rainwater and enter rivers or lakes. In the long run, it is easy to cause eutrophication pollution of rivers or lakes. In order to solve the above problems, the use of slow-release fertilizers can solve the above problems well.

[0005] Patent CN100558682C provides a polymer coated controlled release fertilizer and its production method and special coating material. The coating material of the controlled release fertilizer in the patent includes branched acrylic acid grafted low-density polyethylene with an average molecular weight between 20,000 and 30,000 Daltons and acrylic acid grafted low-density polyethylene with an average molecular weight between 20,000 and 30,000 Daltons; the mass fraction ratio of the branched acrylic acid grafted low-density polyethylene and the acrylic acid grafted low-density polyethylene is 1:0.33-1. However, the coated fertilizer prepared by the patent is not easy to degrade and is easy to cause white pollution. The document "Degradation characteristics of residual film of nano TiO2-LDPE composite coated controlled release fertilizer" prepares nano TiO2-LDPE composite coated controlled release fertilizer by compounding nano TiO2 and acrylic acid grafted low-density polyethylene to form a coating liquid, and using a spouted fluidized bed coating device. The fertilizer has photodegradable properties, but the slow release ability of the fertilizer prepared by the document and the prior art is still poor. Summary of the invention

[0006] In order to solve the problem of poor sustained-release ability of the fertilizer prepared by the prior art in the background art, the object of the present invention is to provide a fulvic acid enhanced formula fertilizer and a preparation method thereof.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A fulvic acid enhanced formula fertilizer comprises the following raw materials by weight: 80-90 parts of fertilizer particles and 20-35 parts of coating solution. The coating solution is composed of iron-doped modified titanium dioxide and acrylic acid grafted low-density polyethylene and tetrachloroethylene. The iron-doped modified titanium dioxide is modified titanium dioxide loaded with iron ions, and the modified titanium dioxide is titanium dioxide treated with 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate.

[0009] Further, the fertilizer granules are prepared by the following steps:

[0010] Dissolve fulvic acid in water to obtain a mixture a; dissolve nitrogen, phosphorus and potassium fertilizers and trace elements in water to obtain a mixture b; add the mixture a to the mixture b, stir, and then perform spray drum granulation to obtain fertilizer granules, and control the size of the fertilizer granules to be 2.5-3 mm.

[0011] The dosage ratio of humic acid to water is 60-90 g:500 mL; the dosage ratio of nitrogen, phosphorus and potassium fertilizers, trace elements and water is 1.5-1.7 kg:5-8 g:2 L; and the volume ratio of mixed solution a and mixed solution b is 1:12.5.

[0012] Furthermore, the nitrogen, phosphorus and potassium fertilizers include the following raw materials in parts by weight: 10-50 parts of nitrogen fertilizer, 16-40 parts of phosphorus fertilizer, and 20-50 parts of potassium fertilizer.

[0013] Furthermore, the nitrogen fertilizer is one or more of urea, ammonium nitrate, ammonium sulfate, and ammonium chloride.

[0014] Furthermore, the phosphate fertilizer is one or more of monoammonium phosphate, diammonium phosphate, and potassium dihydrogen phosphate.

[0015] Furthermore, the potash fertilizer is one or more of potassium chloride, potassium sulfate and potassium nitrate.

[0016] Furthermore, the trace elements are a mixture of zinc sulfate heptahydrate, manganese sulfate, and ammonium molybdate in a mass ratio of 1:1:1.

[0017] Further, the coating solution is prepared by the following steps:

[0018] The iron-doped modified titanium dioxide and the acrylic acid-grafted low-density polyethylene were mixed and added into a dissolving tank containing tetrachloroethylene, and stirred at 110° C. for 20-30 minutes to obtain a coating solution;

[0019] The dosage ratio of iron-doped modified titanium dioxide, acrylic acid grafted low-density polyethylene and tetrachloroethylene is 0.05-0.2g:10g:100-150mL.

[0020] Further, the iron-doped modified titanium dioxide is prepared by the following steps:

[0021] Step A1: tetrabutyl titanate, anhydrous ethanol and glacial acetic acid are mixed, the pH is adjusted to 2.5-3.5, and stirred for 40-50 minutes to form a sol; the sol is aged for 24 hours, dried at 90° C. for 12 hours to obtain a dry gel, and then ground and calcined in a muffle furnace for 2 hours to obtain titanium dioxide powder;

[0022] Wherein, the volume ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 1-1.25:2-2.5:0.15-0.25.

[0023] Step A2: Add titanium dioxide powder and 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate to a 60% volume fraction ethanol aqueous solution, stir for 20-30 minutes, ultrasonicate for 5 minutes, react at room temperature for 3-5 hours, filter, wash with ethanol, and vacuum dry to obtain modified titanium dioxide.

[0024] The dosage ratio of titanium dioxide powder, 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate and 60% ethanol aqueous solution is 3g: 0.01-0.05g: 80-100mL.

[0025] Step A3: adding modified titanium dioxide and ferric nitrate to a 60% by volume ethanol aqueous solution, stirring for 30-40 min, ultrasonicating for 10-20 min, reacting at room temperature for 4-6 h, filtering, washing with ethanol, and vacuum drying to obtain iron-doped modified titanium dioxide;

[0026] The dosage ratio of modified titanium dioxide, ferric nitrate and 60% ethanol aqueous solution is 3g: 0.03-0.21g: 80-100mL.

[0027] In the above step A2, 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate is an organic cationic surfactant, which can improve the dispersibility of titanium dioxide powder.

[0028] Further, the acrylic acid grafted low-density polyethylene is prepared by the following steps:

[0029] Benzophenone is dissolved in a 10 wt% acrylic acid solution, and then low-density polyethylene is added, and ultraviolet light is irradiated at 25° C. for 3-5 minutes, and excess ungrafted acrylic acid is removed by acetone extraction, and then dried to obtain acrylic acid-grafted low-density polyethylene.

[0030] The dosage ratio of benzophenone, acrylic acid solution and low-density polyethylene is 0.5-1g:10mL:100g.

[0031] A method for preparing a fulvic acid synergistic formula fertilizer comprises the following steps:

[0032] The fertilizer granules are placed in a spray drum granulator, and the coating solution is coated on the surface of the fertilizer granules while the granules are rotating. The granules are dried in an oven at 30°C to obtain fulvic acid enhanced formula fertilizer, and the particle size of the fertilizer granules is controlled to be 4-6 mm.

[0033] Beneficial effects of the present invention:

[0034] 1. The present invention adopts iron-doped modified titanium dioxide and acrylic acid grafted low-density polyethylene to mix to prepare a coating solution. The iron-doped modified titanium dioxide contains 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate, which can enhance the stability of the coating material through physical entanglement and formation of non-covalent bonds with acrylic acid grafted low-density polyethylene, thereby improving the slow-release ability of the fertilizer. Due to the slow release of nutrients, crops can more fully absorb and utilize the nutrients in the fertilizer, reducing the loss and waste of nutrients, thereby improving the utilization rate of the fertilizer.

[0035] 2. 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate is an organic cationic surfactant that can improve the dispersibility of titanium dioxide powder. It allows titanium dioxide powder to be evenly filled in acrylic acid grafted low-density polyethylene, has an enhanced effect on the controlled release of acrylic acid grafted low-density polyethylene, and enhances the slow-release ability of the fertilizer.

[0036] 3. The iron-doped modified titanium dioxide powder contains trivalent iron ions. The incorporation of iron will form impurity energy levels, and photons with less energy can also undergo transitions, thereby red-shifting its absorption of light, expanding the light response range, resulting in improved photocatalytic efficiency, and thus improving the degradability of the fertilizer coating material prepared by the present invention, reducing pollution to the environment. In addition, the modified titanium dioxide powder containing sulfonic acid groups can further chelate with iron ions, which is conducive to the uniform distribution of iron elements on the surface of the fertilizer coating material, further improving the photocatalytic activity, and improving the degradability of the fertilizer coating material. After the coating material is degraded, this part of the iron ions can also be used as trace elements to provide nutrients for plant growth. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The molecular weight of the low-density polyethylene in the present invention is 40700, and it is purchased from Beijing Yanhua Petrochemical Co., Ltd.

[0039] Preparation Example 1

[0040] The iron-doped modified titanium dioxide of this preparation example is prepared by the following steps:

[0041] Step A1: 10 mL of tetrabutyl titanate, 20 mL of anhydrous ethanol, and 1.5 mL of glacial acetic acid were mixed, the pH was adjusted to 2.5-3.5, and stirred for 40 min to form a sol; the sol was aged for 24 h, dried at 90° C. for 12 h to obtain a dry gel, and after grinding, it was placed in a muffle furnace and calcined for 2 h to obtain titanium dioxide powder;

[0042] Step A2: Add 3 g of titanium dioxide powder and 0.01 g of 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate to 80 mL of 60% ethanol aqueous solution, stir for 20 min, ultrasonicate for 5 min, react at room temperature for 3 h, filter, wash with ethanol, and dry in vacuum to obtain modified titanium dioxide.

[0043] Step A3: Add 3 g of modified titanium dioxide and 0.03 g of ferric nitrate to 80 mL of 60% ethanol aqueous solution, stir for 30 min, ultrasonicate for 10 min, react at room temperature for 4 h, filter, wash with ethanol, and vacuum dry to obtain iron-doped modified titanium dioxide;

[0044] Preparation Example 2

[0045] The iron-doped modified titanium dioxide of this preparation example is prepared by the following steps:

[0046] Step A1: 11 mL of tetrabutyl titanate, 23 mL of anhydrous ethanol, and 2 mL of glacial acetic acid were mixed, the pH was adjusted to 2.5-3.5, and stirred for 45 min to form a sol; the sol was aged for 24 h, dried at 90 ° C for 12 h to obtain a dry gel, and then ground and calcined in a muffle furnace for 2 h to obtain titanium dioxide powder;

[0047] Step A2: Add 3 g of titanium dioxide powder and 0.03 g of 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate to 90 mL of 60% ethanol aqueous solution, stir for 25 min, ultrasonicate for 5 min, react at room temperature for 4 h, filter, wash with ethanol, and dry in vacuum to obtain modified titanium dioxide.

[0048] Step A3: Add 3 g of modified titanium dioxide and 0.14 g of ferric nitrate to 90 mL of 60% ethanol aqueous solution, stir for 35 min, ultrasonicate for 15 min, react at room temperature for 5 h, filter, wash with ethanol, and vacuum dry to obtain iron-doped modified titanium dioxide;

[0049] Preparation Example 3

[0050] The iron-doped modified titanium dioxide of this preparation example is prepared by the following steps:

[0051] Step A1: 12.5 mL of tetrabutyl titanate, 25 mL of anhydrous ethanol, and 2.5 mL of glacial acetic acid were mixed, the pH was adjusted to 2.5-3.5, and stirred for 45 min to form a sol; the sol was aged for 24 h, dried at 90° C. for 12 h to obtain a dry gel, and after grinding, it was placed in a muffle furnace and calcined for 2 h to obtain titanium dioxide powder;

[0052] Step A2: Add 3 g of titanium dioxide powder and 0.05 g of 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate to 100 mL of 60% ethanol aqueous solution, stir for 30 min, ultrasonicate for 5 min, react at room temperature for 5 h, filter, wash with ethanol, and dry in vacuum to obtain modified titanium dioxide.

[0053] Step A3: Add 3 g of modified titanium dioxide and 0.21 g of ferric nitrate to 100 mL of 60% ethanol aqueous solution, stir for 40 min, ultrasonicate for 20 min, react at room temperature for 6 h, filter, wash with ethanol, and vacuum dry to obtain iron-doped modified titanium dioxide;

[0054] Preparation Example 4

[0055] The difference between this preparation example and preparation example 1 is that "3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate" in step A2 of preparation example 1 is replaced by "trimethoxysilane", and the remaining raw materials, processes and parameters are the same as those in preparation example 1.

[0056] Preparation Example 5

[0057] This preparation example is modified titanium dioxide, and the preparation process of modified titanium dioxide is the same as steps A1-A2 of Preparation Example 1.

[0058] Preparation Example 6

[0059] The present preparation example is different from the preparation example 1 in that the acrylic acid grafted low-density polyethylene in the preparation example 1 is replaced by low-density polyethylene, and the other raw materials, processes and parameters are the same as those in the preparation example 1.

[0060] Preparation Example 7

[0061] The coating solution of this preparation example is prepared by the following steps:

[0062] 0.05 g of the iron-doped modified titanium dioxide prepared in Preparation Example 1 and 10 g of acrylic acid-grafted low-density polyethylene were mixed and added into a dissolving tank containing 100 mL of tetrachloroethylene, and stirred at 110° C. for 20 min to obtain a coating solution.

[0063] Acrylic acid grafted low-density polyethylene is made by the following steps:

[0064] 0.5 g of benzophenone was dissolved in 10 mL of 10 wt % acrylic acid solution, and then 100 g of low-density polyethylene was added. The mixture was irradiated with ultraviolet light at 25° C. for 3 min, and the excess ungrafted acrylic acid was removed by acetone extraction. The mixture was dried to obtain acrylic acid-grafted low-density polyethylene.

[0065] Preparation Example 8

[0066] The coating solution of this preparation example is prepared by the following steps:

[0067] 0.1 g of the iron-doped modified titanium dioxide prepared in Preparation Example 2 and 10 g of acrylic acid-grafted low-density polyethylene were mixed and added into a dissolving tank containing 125 mL of tetrachloroethylene, and stirred at 110° C. for 25 min to obtain a coating solution.

[0068] Acrylic acid grafted low-density polyethylene is made by the following steps:

[0069] 0.75 g of benzophenone was dissolved in 10 mL of 10 wt % acrylic acid solution, and then 100 g of low-density polyethylene was added. The mixture was irradiated with ultraviolet light at 25° C. for 4 min, and the excess ungrafted acrylic acid was removed by acetone extraction. The mixture was dried to obtain acrylic acid-grafted low-density polyethylene.

[0070] Preparation Example 9

[0071] The coating solution of this preparation example is prepared by the following steps:

[0072] 0.2 g of the iron-doped modified titanium dioxide prepared in Preparation Example 3 and 10 g of acrylic acid-grafted low-density polyethylene were mixed and added into a dissolving tank containing 150 mL of tetrachloroethylene, and stirred at 110° C. for 30 min to obtain a coating solution.

[0073] Acrylic acid grafted low-density polyethylene is made by the following steps:

[0074] 1 g of benzophenone was dissolved in 10 mL of 10 wt% acrylic acid solution, and then 100 g of low-density polyethylene was added. The mixture was irradiated with ultraviolet light at 25° C. for 5 min, and the excess ungrafted acrylic acid was removed by acetone extraction. The mixture was dried to obtain acrylic acid-grafted low-density polyethylene.

[0075] Preparation Example 10

[0076] The preparation method of the coating solution in this preparation example is different from that in Preparation Example 7, in that the iron-doped modified titanium dioxide and acrylic acid-grafted low-density polyethylene in Preparation Example 7 are replaced by the product prepared in Preparation Example 4, and the remaining raw materials, processes and parameters are the same as those in Preparation Example 7.

[0077] Preparation Example 11

[0078] The preparation method of the coating solution in this preparation example is different from that in Preparation Example 7, in that the iron-doped modified titanium dioxide acrylic acid grafted low-density polyethylene in Preparation Example 7 is replaced by the product prepared in Preparation Example 5, and the remaining raw materials, processes and parameters are the same as those in Preparation Example 7.

[0079] Preparation Example 12

[0080] The preparation method of the coating solution in this preparation example is different from that in Preparation Example 7, in that the iron-doped modified titanium dioxide and acrylic acid-grafted low-density polyethylene in Preparation Example 7 are replaced by the product prepared in Preparation Example 6, and the remaining raw materials, processes and parameters are the same as those in Preparation Example 7.

[0081] Example 1

[0082] A fulvic acid enhanced formula fertilizer comprises the following raw materials in parts by weight: 80 parts of fertilizer granules and 20 parts of coating solution prepared in Preparation Example 7.

[0083] The fertilizer granules are made by the following steps:

[0084] Dissolve 40g of fulvic acid in 160mL of water to obtain a mixture a; dissolve 1.5kg of nitrogen, phosphorus and potassium fertilizers and 5g of trace elements in 2L of water to obtain a mixture b; add 160mL of the mixture a to 2L of the mixture b, stir, and then perform spray drum granulation to obtain fertilizer granules, and control the particle size of the fertilizer granules to be 2.5-3mm.

[0085] Among them, the nitrogen, phosphorus and potassium fertilizer includes the following raw materials in parts by weight: 10 parts of urea, 40 parts of monoammonium phosphate, and 50 parts of potassium chloride; the trace elements are a mixture of zinc sulfate heptahydrate, manganese sulfate, and ammonium molybdate in a mass ratio of 1:1:1.

[0086] The preparation method of the fulvic acid synergistic formula fertilizer is as follows:

[0087] The fertilizer granules are placed in a spray drum granulator, and the coating solution is coated on the surface of the fertilizer granules while the granules are rotating. The granules are dried in an oven at 30°C to obtain fulvic acid enhanced formula fertilizer, and the particle size of the fertilizer granules is controlled to be 4-6 mm.

[0088] Example 2

[0089] A fulvic acid enhanced formula fertilizer comprises the following raw materials in parts by weight: 85 parts of fertilizer granules and 30 parts of coating solution prepared in Preparation Example 8.

[0090] The fertilizer granules are made by the following steps:

[0091] Dissolve 50g of fulvic acid in 160mL of water to obtain a mixture a; dissolve 1.6kg of nitrogen, phosphorus and potassium fertilizers and 6g of trace elements in 2L of water to obtain a mixture b; add 160mL of the mixture a to 2L of the mixture b, stir, and then perform spray drum granulation to obtain fertilizer granules, and control the particle size of the fertilizer granules to be 2.5-3mm.

[0092] Among them, the nitrogen, phosphorus and potassium fertilizer includes the following raw materials in parts by weight: 15 parts of urea, 15 parts of ammonium nitrate, 15 parts of monoammonium phosphate, 15 parts of potassium dihydrogen phosphate, 15 parts of potassium chloride, and 15 parts of potassium sulfate; the trace elements are a mixture of zinc sulfate heptahydrate, manganese sulfate, and ammonium molybdate in a mass ratio of 1:1:1.

[0093] The preparation method of the fulvic acid synergistic formula fertilizer is as follows:

[0094] The fertilizer granules are placed in a spray drum granulator, and the coating solution is coated on the surface of the fertilizer granules while the granules are rotating. The granules are dried in an oven at 30°C to obtain fulvic acid enhanced formula fertilizer, and the particle size of the fertilizer granules is controlled to be 4-6 mm.

[0095] Example 3

[0096] A fulvic acid enhanced formula fertilizer comprises the following raw materials in parts by weight: 90 parts of fertilizer granules and 35 parts of coating solution prepared in Preparation Example 9.

[0097] The fertilizer granules are made by the following steps:

[0098] Dissolve 60g of humic acid in 160mL of water to obtain a mixture a; dissolve 1.7kg of nitrogen, phosphorus and potassium fertilizers and 8g of trace elements in 2L of water to obtain a mixture b; add 160mL of the mixture a to 2L of the mixture b, stir, and then perform spray drum granulation to obtain fertilizer granules, and control the particle size of the fertilizer granules to be 2.5-3mm.

[0099] Among them, the nitrogen, phosphorus and potassium fertilizer includes the following raw materials in parts by weight: 10 parts of urea, 20 parts of ammonium nitrate, 20 parts of ammonium chloride, 10 parts of monoammonium phosphate, 6 parts of diammonium phosphate, and 20 parts of potassium nitrate; the trace elements are a mixture of zinc sulfate heptahydrate, manganese sulfate, and ammonium molybdate in a mass ratio of 1:1:1.

[0100] The preparation method of the fulvic acid synergistic formula fertilizer is as follows:

[0101] The fertilizer granules are placed in a spray drum granulator, and the coating solution is coated on the surface of the fertilizer granules while the granules are rotating. The granules are dried in an oven at 30°C to obtain fulvic acid enhanced formula fertilizer, and the particle size of the fertilizer granules is controlled to be 4-6 mm.

[0102] Comparative Example 1

[0103] The raw materials and steps of this comparative example are the same as those of Example 1, except that the coating solution uses the material prepared in Preparation Example 10.

[0104] Comparative Example 2

[0105] The raw materials and steps of this comparative example are the same as those of Example 1, except that the coating solution uses the material prepared in Preparation Example 11.

[0106] Comparative Example 3

[0107] The raw materials and steps of this comparative example are the same as those of Example 1, except that the coating solution uses the material prepared in Preparation Example 12.

[0108] The performance of the fulvic acid synergistic formula fertilizer prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 was tested, and the test items were as follows:

[0109] 1. Sustained release: Determined by water dissolution rate method according to GB / T 23348-2009; 10 g of the synergistic fertilizer prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was weighed and put into a small bag made of 100-mesh nylon gauze, the small bag was put into a 250 mL glass bottle, 200 mL of water was added, the bottle was sealed with a cover, and placed in a 25°C biochemical constant temperature incubator, and samples were taken at 1, 7, 16, 23, 34, 56, and 70 days, and the nitrogen release was tested by an automatic analyzer, and the cumulative nitrogen release rate was calculated. The calculation formula is as follows: nitrogen release rate = Wn / W, where Wn is the mass fraction of the nitrogen release measured on the nth day, and W is the mass fraction of the total nitrogen. The test results are shown in Table 1.

[0110] 2. Synergistic test: 200g of the synergistic fertilizer prepared by Example 1-Example 3 and Comparative Example 1-Comparative Example 3 was taken and dissolved in 1L of water, and a soil potted test of pakchoi was carried out in a greenhouse. A total of 30 pakchoi plants were planted. During the period of three leaves and one heart of pakchoi, the three synergistic fertilizers were evenly sprayed on the leaves of 10 pakchoi plants until they were wet. The second and third sprays were applied on the 5th and 10th days after the first spraying. One month after the third spraying, the pakchoi was harvested, and the fresh weight and dry weight of the aboveground part and root system of the pakchoi were measured. The test results are shown in Table 2.

[0111] 3. Degradation performance: The residual film is the residual film of the controlled-release fertilizer that has been dissolved. That is, a small hole is pierced in the fertilizer coating film, and the fertilizer is completely dissolved after being soaked in water. The residual film is placed in a self-made photolysis box. The light source is two 30W ultraviolet lamps with a main wavelength of 254nm. The watch glass is 15cm away from the ultraviolet light source. The photocatalytic process is carried out at room temperature. Samples are taken at regular intervals to calculate the weight loss rate of the residual film. The test results are shown in Table 3.

[0112] Table 1

[0113]

[0114]

[0115] Note: The nitrogen dissolution rate of Comparative Example 1 reached 100% on the 66th day, the nitrogen dissolution rate of Comparative Example 2 reached 100% on the 65th day, and the nitrogen dissolution rate of Comparative Example 3 reached 100% on the 63rd day.

[0116] It can be seen from Table 1 that the controlled release ability of the fulvic acid synergistic formula fertilizer prepared in Examples 1-3 is better than that of the fulvic acid synergistic formula fertilizer prepared in Comparative Examples 1-3. Comparative Example 1 does not contain sulfonic acid groups and quaternary ammonium salts, and the physical entanglement and non-covalent bonds between the acrylic acid grafted low-density polyethylene are reduced, thereby reducing the stability of the coating material and reducing the slow-release performance. Comparative Example 2 does not contain sulfonic acid groups, quaternary ammonium salt groups and iron ions, and the physical entanglement and non-covalent bonds between the acrylic acid grafted low-density polyethylene are reduced, thereby reducing the stability of the coating material and reducing the slow-release performance. Comparative Example 3 does not contain acrylic acid, which shows that acrylic acid grafted low-density polyethylene helps to improve the slow-release ability of the fertilizer.

[0117] Table 2

[0118]

[0119]

[0120] It can be seen from Table 2 that the ability of the fulvic acid synergistic formula fertilizers prepared in Examples 1-3 to promote crop growth is better than that of the fulvic acid synergistic formula fertilizers prepared in Comparative Examples 1-3, indicating that the chelation between the sulfonic acid group and the iron ions helps to evenly distribute the iron elements on the surface of the fertilizer. This part of the iron ions can serve as trace elements to provide nutrients for plant growth.

[0121] Table 3

[0122] project 3d weight loss rate 6d weight loss rate 13d weight loss rate 18d weight loss rate Example 1 2.8% 3.3% 7.6% 9.3% Example 2 5.3% 7.8% 12.3% 15.4% Example 3 6.9% 9.1% 15.4% 16.2% Comparative Example 1 2.6% 3.1% 6.7% 8.9% Comparative Example 2 2.2% 2.4% 5.3% 7.3% Comparative Example 3 2.5% 2.9% 6.5% 9.2%

[0123] It can be seen from Table 3 that the degradation efficiency of the residual film prepared in Examples 1-3 is better than that of the residual film prepared in Comparative Examples 1-3. The iron ions in Comparative Example 1 do not form chelates, and the degradation ability is reduced, indicating that the modified titanium dioxide powder containing sulfonic acid groups can further chelate with iron ions, which is conducive to the uniform distribution of iron elements on the surface of the fertilizer coating material, further improving the photocatalytic activity, and improving the degradability of the fertilizer coating material. Comparative Example 2 does not contain iron ions, and the degradation ability is significantly reduced, indicating that the incorporation of iron will form impurity energy levels, and photons with lower energy can also undergo transitions, thereby red-shifting its absorption of light, expanding the light response range, resulting in improved photocatalytic efficiency, and thus improving the degradability of the fertilizer coating material prepared by the present invention.

[0124] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0125] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fulvic acid synergistic formula fertilizer, characterized in that: The method comprises the following raw materials in parts by weight: 80-90 parts of fertilizer granules and 20-35 parts of coating solution; The coating solution is composed of iron-doped modified titanium dioxide and acrylic acid grafted low-density polyethylene and tetrachloroethylene. The iron-doped modified titanium dioxide is modified titanium dioxide loaded with iron ions, and the modified titanium dioxide is titanium dioxide treated with 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate.

2. The fulvic acid synergistic formula fertilizer according to claim 1, characterized in that: Fertilizer granules are made through the following steps: Dissolve fulvic acid in water to obtain a mixture a; dissolve nitrogen, phosphorus and potassium fertilizers and trace elements in water to obtain a mixture b; add the mixture a to the mixture b, stir, and then perform spray drum granulation to obtain fertilizer granules, and control the size of the fertilizer granules to be 2.5-3 mm.

3. The fulvic acid synergistic formula fertilizer according to claim 2, characterized in that: The dosage ratio of humic acid to water is 60-90g:500mL; the dosage ratio of nitrogen, phosphorus and potassium fertilizers, trace elements and water is 1.5-1.7kg:5-8g:2L; the volume ratio of mixed solution a and mixed solution b is 1:12.

5.

4. The fulvic acid synergistic formula fertilizer according to claim 2, characterized in that: The nitrogen, phosphorus and potassium fertilizers include the following raw materials in parts by weight: 10-50 parts of nitrogen fertilizer, 16-40 parts of phosphorus fertilizer, and 20-50 parts of potassium fertilizer; Among them, the nitrogen fertilizer is one or more of urea, ammonium nitrate, ammonium sulfate, and ammonium chloride; the phosphate fertilizer is one or more of monoammonium phosphate, diammonium phosphate, and potassium dihydrogen phosphate; the potassium fertilizer is one or more of potassium chloride, potassium sulfate, and potassium nitrate; and the trace elements are a mixture of zinc sulfate heptahydrate, manganese sulfate, and ammonium molybdate in a mass ratio of 1:1:

1.

5. The fulvic acid synergistic formula fertilizer according to claim 1, characterized in that: The coating solution is prepared by the following steps: mixing iron-doped modified titanium dioxide, acrylic acid-grafted low-density polyethylene, and tetrachloroethylene, and stirring at 110° C. for 20-30 minutes to obtain a coating solution; The dosage ratio of iron-doped modified titanium dioxide, acrylic acid grafted low-density polyethylene and tetrachloroethylene is 0.05-0.2g:10g:100-150mL.

6. The fulvic acid synergistic formula fertilizer according to claim 5, characterized in that: Iron-doped modified titanium dioxide is prepared by the following steps: Step A1: tetrabutyl titanate, anhydrous ethanol and glacial acetic acid are mixed, the pH is adjusted to 2.5-3.5, and stirred for 40-50 minutes to form a sol; the sol is aged for 24 hours, dried at 90° C. for 12 hours to obtain a dry gel, and then ground and calcined in a muffle furnace for 2 hours to obtain titanium dioxide powder; Step A2: adding titanium dioxide powder and 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate to a 60% ethanol aqueous solution, stirring for 20-30 min, ultrasonicating for 5 min, reacting at room temperature for 3-5 h, filtering, washing with ethanol, and vacuum drying to obtain modified titanium dioxide; Step A3: Add modified titanium dioxide and ferric nitrate to a 60% by volume ethanol aqueous solution, stir for 30-40 minutes, ultrasonicate for 10-20 minutes, react at room temperature for 4-6 hours, filter, wash with ethanol, and vacuum dry to obtain iron-doped modified titanium dioxide.

7. The fulvic acid synergistic formula fertilizer according to claim 6, characterized in that: In step A1, the volume ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 1-1.25:2-2.5:0.15-0.25; in step A2, the amount ratio of titanium dioxide powder, 3-{[dimethyl(3-trimethoxysilyl)propyl]ammonium}-propane-1-sulfonate and 60% ethanol aqueous solution is 3g:0.01-0.05g:80-100mL; in step A3, the amount ratio of modified titanium dioxide, ferric nitrate and 60% ethanol aqueous solution is 3g:0.03-0.21g:80-100mL.

8. The fulvic acid synergistic formula fertilizer according to claim 5, characterized in that: Acrylic acid grafted low-density polyethylene is made by the following steps: Benzophenone was dissolved in a 10 wt% acrylic acid solution, and then low-density polyethylene was added, and ultraviolet light was irradiated at 25° C. for 3-5 minutes, and acetone was extracted and dried to obtain acrylic acid-grafted low-density polyethylene.

9. The fulvic acid synergistic formula fertilizer according to claim 8, characterized in that: The usage ratio of benzophenone, acrylic acid solution and low-density polyethylene is 0.5-1g:10mL:100g.

10. A method for preparing a fulvic acid synergistic formula fertilizer according to any one of claims 1 to 9, characterized in that: The following steps are involved: The fertilizer granules are placed in a spray drum granulator, and the coating solution is coated on the surface of the fertilizer granules while the granules are rotating. The granules are dried in an oven at 30°C to obtain fulvic acid enhanced formula fertilizer, and the particle size of the fertilizer granules is controlled to be 4-6 mm.

Citation Information

Patent Citations

  • Controlled fertilizer of polymer capsule, production method, and dedicated capsule material

    CN100558682C

Cited By

  • Fulvic acid grass control fertilizer suitable for flying application of unmanned aerial vehicle and preparation method of fulvic acid grass control fertilizer

    CN121318614A